2023
DOI: 10.1049/bsb2.12070
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of titanium carbide coating on Ti15Mo alloy and its tribological behaviour

Hongxiang Wang,
Jiajia Shen,
Weipeng Zhang
et al.

Abstract: Ti15Mo alloy has been regarded as one of the most potential biomedical materials due to its excellent performance. However, the low hardness and poor wear resistance of titanium alloy limit the further application. Therefore, high temperature solid carburising technology was performed on the surface of Ti15Mo alloys to prepare titanium carbide (TiC) coating with graphene (G) as the carburising agent. The microstructure, mechanical properties, and tribological properties of TiC coating under different lubricant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The in vitro cell test clearly showed there was no effect on cell differentiation for chemical polishing. Ti metal as a biologically inert materials was used wildly in the bone implant area [39,40]. He et al found the Ti implant polished by HF/HNO 3 solution had good biocompatibility [41].…”
Section: In Vitro Cell Testmentioning
confidence: 99%
“…The in vitro cell test clearly showed there was no effect on cell differentiation for chemical polishing. Ti metal as a biologically inert materials was used wildly in the bone implant area [39,40]. He et al found the Ti implant polished by HF/HNO 3 solution had good biocompatibility [41].…”
Section: In Vitro Cell Testmentioning
confidence: 99%